Termination of architect's engagement - Zolkafli @ Zulkifli, Umi Kalsum (2008)
Issuance of Certificate Completion and Compliance (CCC) by Professional Architect has made the role of Professional Architect become more important. Professional Architect is required to become Prinsipal Submitting Person to the Local Authority. Certificate of Completion and Compliance will be issued after getting clearance from all the respective department of Local Authority. Therefore termination of Architect’s Engagement will create a lot of problem to the construction contract. Problem that may arise is withholding of Letter of Release by the Professional Architect whereby the client may have problem in appointing a new Professional Architect to proceed with the works. Is Professional Architect allowed to withholding the Letter of Release? Therefore the aim of this research is to ensure whether a Professional Architect can with holding the Letter of Release or not. The research scope will be limited to the Contract of Services between the Professional Architect and the Client in Malaysia. The research methodology is by analyzing cases regarding issue on Letter of Release, Interview with Professional Architect, Developer and Lawyers and the most important is by referring to the Architect Act 1967 (Act 117) & Architect Rules 1996. After analyzing the information, it shows that Professional Architect cannot with holding Letter of Release because that the architect can hold the client for ransom. From the research it can be concluded that Client have to comply with their obligation under the contract between the Professional Architect especially when matter on payment of consultant fees and if dispute arise it must be referred to Arbitration, Mediation or Court.